2011
DOI: 10.1007/s10495-011-0634-9
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-1 receptor activation prevents hydrogen peroxide-induced oxidative stress, mitochondrial dysfunction and apoptosis

Abstract: Vascular disease is the leading cause of morbidity and mortality. Oxidative stress can cause endothelial cell apoptosis. Low insulin like growth factor-1 (IGF-1) has been linked to adverse risk profile and increased vascular disease incidence. Since IGF-1 acts as an important survival factor for multiple cell types, we undertook this study to investigate whether IGF-1 favorably affects oxidative-stress mediated apoptosis of vascular endothelial cells. Exposure to hydrogen peroxide induced apoptotic changes (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Computational analysis suggested that human IGF1R, a key antiapoptosis gene in ECs, has a miR‐223 binding site in its 3′ untranslated region that is conserved among mouse, rat, and human . IGF1R is thus a potential direct target gene of miR‐223.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational analysis suggested that human IGF1R, a key antiapoptosis gene in ECs, has a miR‐223 binding site in its 3′ untranslated region that is conserved among mouse, rat, and human . IGF1R is thus a potential direct target gene of miR‐223.…”
Section: Resultsmentioning
confidence: 99%
“…Computational analysis suggested that human IGF1R, a key antiapoptosis gene in ECs, has a miR-223 binding site in its 3 0 untranslated region that is conserved among mouse, rat, and human. 12,17 IGF1R is thus a potential direct target gene of miR-223. To test whether miR-223 is able to bind directly to IGF1R and inhibit its expression, a construct in which a fragment of the 3 0 untranslated region of IGF1R mRNA containing the conserved miR-223 binding sequence was cloned into a firefly luciferase reporter construct and transfected into HEK 293 cells.…”
Section: Igf1r Is a Signaling Pathway Involved In Mir-223-mediated Efmentioning
confidence: 99%
“…It is significant that in vitro treatment of endothelial cells and cardiomyocytes with recombinant IGF-1 decreases mitochondrial H 2 O 2 production (29). Treatment of cultured endothelial cells with IGF-1 also preserves ⌬ m , maintaining the mitochondrial retention of cytochrome c and reducing caspase-3 activation upon exposure to H 2 O 2 (76). Furthermore, overexpression of IGF-1 protects mice against high-fat diet feeding-induced increases in ROS generation, thus preventing mitochondrial damage (227).…”
Section: Mechanisms Of Mitochondrial Dysfunction and Altered Mitochonmentioning
confidence: 99%
“…1). In fact, it has been reported that IGF-I improves mitochondrial function in vitro [53] and in vivo [54]. IGF-IR activation prevented oxidative stress, mitochondrial dysfunction, and apoptosis in human umbilical vein endothelial cells (HUVEC) [53].…”
Section: Igf-i Action In Livermentioning
confidence: 99%